Fracture strength of electroslag welding joint with high-performance steel. (February 2019) - Iyama, Jun; Matsumoto, Yuka; Ishii, Takumi; Shimokawa, Hiroumi; Nikaido, Masato; Yamada, Satoshi
ABSTRACT: Τo clarify the fracture behavior of electroslag welding (ESW) joints, we used the connection of box-column flange and interior diaphragm made of high-performance steel SA440C. Owing to the large heat input, the ductility and notch toughness of ESW joints are prone to degradation. In particular, because the mechanical properties of high-strength steel are sensitive to the high heat input, the performance of ESW joints may significantly degrade when used with SA440C. In addition, considering the case wherein the beam-to-column connection is under strong seismic excitation, an ESW joint located at the crossing of a column flange, beam flange, and interior diaphragm is subject to biaxial tensile forces, causing premature brittle fracturing. To clarify the performance of ESW joints under such conditions, biaxial tensile loading tests were conducted. Four specimens were fabricated from the built-up box column, with interior diaphragms welded by ESW. Tensile load was statically applied between the interior diaphragm and the beam flange under constant axial load in the column flange. The maximum strength was demonstrated to be governed by the Charpy V-notch (CVN) toughness at the fractured locations. With regard to CVN toughness at the test temperature of the heat-affected zone or weld metal larger than 50 J, the maximum strength was comparable to that of the base metal of SA440C. Highlights: Large-scale electroslag welding joint with high performance steel was tested. Under uni-axial load, fracture occurred from the edge of weld metal. Under bi-axial load, fracture occurred from the heat affected zone. Ultimate strength showed correlation to Charpy V-notch toughness. Strength was high and stable enough where the CVN toughness was higher than 50 J.